Efektifitas Metode Emotional Demonstration terhadap Breastfeeding Self Efficacy (BSE) Ibu Primipara di Kota Bengkulu - Ervina, Lissa; Marsofely, Reka Lagora (UI Scholars Hub, 2025)
Background. Primiparous mothers have a higher risk of experiencing difficulties in providing breast milk (ASI) due to lack of experience and preparation to become mothers. 90% of mothers in Indonesia have breastfed their children, but those who provide exclusively for 6 months are still low at 20%. One of the reasons for the failure of the success of providing exclusive breastfeeding is the low self-confidence or belief (Self Efficacy) of primiparous mothers in providing breast milk. Therefore, it is necessary to provide education about breastfeeding by implementing the emotional demonstration method developed by the Global Alliance for Improved Nutrition (GAIN) to increase breastfeeding self-efficacy in primiparous mothers. Objective. This study aims to determine the effectiveness of the emotional demonstration method in increasing breastfeeding self-efficacy (BSE) in primiparous mothers in Bengkulu City. Method. The research design used quasi-experimental design with two group pretest-posttest design. Data collection used questionnaire instruments. The number of primiparous mother samples was 33 people in the intervention group and 33 people in the control group. Data were analyzed using the Wilcoxon test to determine the differences before and after the intervention. Result. The results of the study showed that there was a difference in Breastfeeding Self Efficacy before and after being given the emotional demonstration method with a p-value = 0.007 (<0.05). Conclusion. The emotional demonstration method has been proven to be effective in increasing Breastfeeding Self Efficacy in primiparous mothers.